A case of Takotsubo cardiomyopathy induced by accidental hypothermia and diabetic ketoacidosis. (3rd April 2013) - Katayama, Yoichi; Hifumi, Toru; Inoue, Junichi; Koido, Yuichi
Abstract : Takotsubo cardiomyopathy is known to be triggered by some stress. We report the first case of Takotsubo cardiomyopathy induced by hypothermia and diabetic ketoacidosis (DKA). A 59-year-old woman was brought to our emergency department. Upon examination, she was found to be lethargic and disoriented. The body temperature was 30.9°C, blood pressure was 86/68 mm Hg, blood glucose level was 1018 mg/dl. Urinalysis revealed the presence of ketones and arterial blood gas analysis revealed pH 6.87. She was diagnosed with DKA and accidental hypothermia. An ECG demonstrated a J wave (V4– 5 ) and ST-segment elevation (V3– 5 ), and an ultrasound cardiogram revealed contractile failure of the left ventricular wall at the apex with hypercontraction of the basal segment. Coronary artery disease was ruled out by coronary angiography, and the diagnosis of Takotsubo cardiomyopathy was confirmed. Physicians should keep in mind that Takotsubo cardiomyopathy can be induced by accidental hypothermia and DKA.